Nutrients and heavy metals mediate the distribution of microbial community in the marine sediments of the Bohai Sea, China. (December 2019) - Lu, Meiqing; Luo, Xin; Jiao, Jiu Jimmy; Li, Hailong; Wang, Xuejing; Gao, Jingyan; Zhang, Xiaolang; Xiao, Kai
Abstract: The Bohai Sea, one of the largest marginal seas in China, is extensively influenced by human and industrial activities. The pollutant loads from anthropogenic activities have induced severe ecological problems. The study investigates the physicochemical characteristics of seawater and sediments in Bohai Bay and Laizhou Bay of the Bohai Sea. The diversity and composition of microbial community in sediments are analyzed by 16S rRNA gene amplicon sequencing. The sequencing results present 16 phyla and 31 classes from the samples. Proteobacteria constituted a dominant phylum, of which the classes of Gamma-, Delta-, and Epsilon- are predominant sub-divisions. Nitrogen, phosphorus, and sulfur cycling related microbes present high abundance in both bays. The metabolism of organic matters is the main factor that influences the distribution of microbial communities in Bohai Bay, while the inflow of Yellow River is the dominant factor that influences the distribution of microbial communities in Laizhou Bay. Sulfur oxidizing process is expected to be positively influenced by heavy metals, while ammonia (NH4 + ) oxidizing process is prone to be negatively affected by heavy metals in both bays. Microbial communities in the offshore sediments of Laizhou Bay and the majority microbial communities in Bohai Bay sediments are subject to similar predominant controlling factors. This phenomenon is likely ascribed to ocean circulation. The results of this study can provide constructive guidelines on ecosystem management of marginal seas in Bohai and elsewhere. Graphical abstract: Image 1 Highlights: Enzyme activities influence the distribution of microbial communities in Bohai Bay. Yellow River influences the distribution of microbial communities in Laizhou Bay. Sulfur reduction oxidizing process is positively influenced by heavy metals. NH4 + oxidizing process is likely to be negatively affected by heavy metals. Abstract : The metabolism of organic matters is the main factor that influences the distribution of microbial communities in Bohai Bay, while the distribution of microbial communities in Laizhou Bay is mainly influenced by the inflow of Yellow River.